2014
DOI: 10.1590/2237-6089-2012-0048
|View full text |Cite
|
Sign up to set email alerts
|

The progression of 102 Brazilian patients with bipolar disorder: outcome of first 12 months of prospective follow-up

Abstract: Introduction: Prospective studies have shown that the course of bipolar disorder (BD) is characterized by the persistence of symptoms, predominantly depression, along most of the time. However, to our knowledge, no studies in Latin America have investigated it. Objectives: To replicate international studies using a Brazilian sample to prospectively analyze treatment outcomes in the first year and to determine potential chronicity factors. Methods: We followed up 102 patients with BD for 12 months and evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…There were 24 studies reporting data on the point prevalence of psychotic symptoms in BD. For an overview of included studies, see online Supplementay Material 5: Studies included in the meta-analyses of the point prevalence of psychotic symptoms in bipolar disorders (Abulseoud et al, 2020;Asaad et al, 2014;Azorin, Adida, & Belzeaux, 2015;Azorin, Akiskal, & Hantouche, 2006;Basterreche et al, 2008;Benazzi, 2001;Bonnin et al, 2015;Caldieraro et al, 2017;Carroll, Vohs, O'Donnell, Shekhar, & Hetrick, 2007;Ciapparelli et al, 2001;Fiedorowicz et al, 2011;Goldberg & Harrow, 2004;Guven, Kesebir, Demirer, & Bilici, 2015;Kessing, 2004;Kessing, Jensen, & Christensen, 2008;Levy & Weiss, 2010;Lindenmayer, Bossie, Kujawa, Zhu, & Canuso, 2008;Lundin, Bartolomeo, O'Donnell, & Hetrick, 2018;Novis et al, 2014;Reddy, Meyer, Wittlin, Miller, & Weinstock, 2017;Salem et al, 2019;Samalin et al, 2014;Schwartzmann et al, 2007;Yildiz, Guleryuz, Ankerst, Ongur, & Renshaw, 2008).…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were 24 studies reporting data on the point prevalence of psychotic symptoms in BD. For an overview of included studies, see online Supplementay Material 5: Studies included in the meta-analyses of the point prevalence of psychotic symptoms in bipolar disorders (Abulseoud et al, 2020;Asaad et al, 2014;Azorin, Adida, & Belzeaux, 2015;Azorin, Akiskal, & Hantouche, 2006;Basterreche et al, 2008;Benazzi, 2001;Bonnin et al, 2015;Caldieraro et al, 2017;Carroll, Vohs, O'Donnell, Shekhar, & Hetrick, 2007;Ciapparelli et al, 2001;Fiedorowicz et al, 2011;Goldberg & Harrow, 2004;Guven, Kesebir, Demirer, & Bilici, 2015;Kessing, 2004;Kessing, Jensen, & Christensen, 2008;Levy & Weiss, 2010;Lindenmayer, Bossie, Kujawa, Zhu, & Canuso, 2008;Lundin, Bartolomeo, O'Donnell, & Hetrick, 2018;Novis et al, 2014;Reddy, Meyer, Wittlin, Miller, & Weinstock, 2017;Salem et al, 2019;Samalin et al, 2014;Schwartzmann et al, 2007;Yildiz, Guleryuz, Ankerst, Ongur, & Renshaw, 2008).…”
Section: Search Resultsmentioning
confidence: 99%
“…For the 11 studies (n = 1263) that gave information about the age span for the included patients, the pooled point prevalence was 45% (95% CI 32-59) (Abulseoud et al, 2020;Asaad et al, 2014;Azorin et al, 2006;Caldieraro et al, 2017;Guven et al, 2015;Levy & Weiss, 2010;Lundin et al, 2018;Novis et al, 2014;Salem et al, 2019;Schwartzmann et al, 2007;Yildiz et al, 2008).…”
Section: Point Prevalence Of Psychotic Symptoms In Bdmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, BD with other comorbid mental illnesses is prevalent in emergency rooms in Latin American countries (Castilla‐Puentes et al ). Besides, a 12‐month study of clients with BD in Brazil showed a predominant recurrence of depressive episodes (Novis et al ). Vázquez et al () in their quantitative study have proven an association between self‐perceived stigma and poor functioning clients with BD, being the only research in Latin America where this association could be demonstrated.…”
Section: Introductionmentioning
confidence: 99%